2022
DOI: 10.3390/ijms23042386
|View full text |Cite
|
Sign up to set email alerts
|

Smart Lipid–Polysaccharide Nanoparticles for Targeted Delivery of Doxorubicin to Breast Cancer Cells

Abstract: In this study, actively-targeted (CD44-receptors) and dual stimuli (pH/redox)-responsive lipid–polymer nanoparticles were proposed as a delivery vehicle of doxorubicin hydrochloride in triple negative breast cancer cell lines. A phosphatidylcholine lipid film was hydrated with a solution of oxidized hyaluronic acid and doxorubicin, chosen as model drug, followed by a crosslinking reaction with cystamine hydrochloride. The obtained spherical nanoparticles (mean diameter of 30 nm) were found to be efficiently in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Since longer circulation times of PEG usually result in reduced endosomal release and will also increase the chances of evoking an anti-PEG immune response [ 51 ], PEG does not seem to possess ideal characteristics for being incorporated in LNPs for in vivo usage. As an alternative, PEG could be replaced with polysaccharides, naturally occurring membrane lipids, or stealth-providing compounds such as polysarcosine to shield the nanoparticle from rapid removal by opsonization [ 52 , 53 , 54 , 55 , 56 ]. Additionally, an attractive concept is passive targeting by changing the lipid formulation, however, little is known about the optimal lipid composition for bone marrow targeting [ 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since longer circulation times of PEG usually result in reduced endosomal release and will also increase the chances of evoking an anti-PEG immune response [ 51 ], PEG does not seem to possess ideal characteristics for being incorporated in LNPs for in vivo usage. As an alternative, PEG could be replaced with polysaccharides, naturally occurring membrane lipids, or stealth-providing compounds such as polysarcosine to shield the nanoparticle from rapid removal by opsonization [ 52 , 53 , 54 , 55 , 56 ]. Additionally, an attractive concept is passive targeting by changing the lipid formulation, however, little is known about the optimal lipid composition for bone marrow targeting [ 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo experiments indicated that DOX@NPs exhibited higher tumor accumulation in 4T1 in situ breast cancer xenografts, achieving targeted delivery and tumor inhibition of DOX ( Figure 2A ). Curcio et al ( Curcio et al, 2022 ) constructed an oxidized hyaluronic acid HA (oxHA) crosslinked by phosphatidylcholine bilayer (PDC) and oxidized disulfide bonding (cystamine hydrochloride-Cys), further loaded with DOX to have an active targeting of CD44 receptor (DOX@PHYN). The nanoparticles were modified by PDC to specifically recognize the CD44 receptor on the surface of TNBC cells, which were mainly manifested by higher uptake in MDA-MB-231 cells, while negligible in the normal MCF-10A cell line.…”
Section: Novel Nano-drug Delivery Systemsmentioning
confidence: 99%
“…Reproduced with permission from Taylor and Francis. (B) Preparation of pH/Redox responsive DOX@PHYN nanoparticles and evaluation of their active targeting level ( Curcio et al, 2022 ). Copyright 2022.…”
Section: Novel Nano-drug Delivery Systemsmentioning
confidence: 99%
“… 6 Compared to conventional drug formulations, NPs are able to overcome pharmacokinetic limitations associated with low solubility, inability to penetrate tumours, and damage to the immune system and other organs. 7 Nanosystems used for cancer treatment include liposomes, 8 polymeric micelles, 9 nanospheres, DNA origami-based nanocarriers, 10 quantum dots, 11 and carbon- 12 and metal- 13 based nanoparticles.…”
Section: Introductionmentioning
confidence: 99%